Structural behaviour of doubly reinforced lightweight concrete wall panel under axial load / Jamilah Abd. Rahim - Abd. Rahim, Jamilah (2010)
Recently, lightweight reinforced concrete walls have gained greater acceptance from many countries in conjunction with the Industrialized Building System (IBS) introduced. Essentially, the system gives many advantages in reducing dead load, the dependency of foreign labour and better investment in technologies, techniques and processes of construction. Lightweight reinforced concrete wall panel has been used in Malaysia in the past few years and still a new construction method. This type of wall may require sequential analysis in making an effective product that gives advantages in all aspects and gives better performance. This research paper analyzes the behaviour doubly reinforced of lightweight wall panel under axial load. The experimental works of wall panel have been done in the Fabrication, Concrete and Heavy Laboratories. There were designed with four samples of wall panels which were D1800NE25D, 1800NE20D, 1800NE15D, 1800NE10D. It was designed as a double layer reinforced wall panel with different slenderness ratio which are 25, 20, 15 and 10…